Centro e periferia nella sintassi dell’infinito italiano e latino - Szilágyi, Imre (Verbum – Analecta Neolatina, 2010)
In the present paper we compare the infinitive structures of Modern Italian and Classical Latin, considering the results of modern linguistics and the dichotomy of centre and periphery. We demonstrate that whereas in modern Italian control structures dominate, in Latin this role is played by the accusative with infinitive. However, the phenomenon of control can be observed in Latin as well even though to a much less extent and under stronger limitations than in Italian. Raising structures have an important role in both languages: their most conspicuous manifestation in Latin is the nominative with infinitive. Another difference between these two languages is that whereas in Italian the infinitive structures show a greater variety (beyond the above mentioned ones there are causative, articled infinitive structures and so on), in Latin practically three structures (accusative with infinitive, nominative with infinitive and control structure) cover the whole range of infinitive structures.